Risk management in a municipal construction enterprise: A theoretical and methodical study - Tworek, Piotr (Journal of Public Governance, 2018)
Objectives: The key aim of the paper is to outline the concept of integrated risk management in municipal construction enterprises, seen as a supportive function that facilitates the overall management of an organisation. What matters most, both in the theory and in practice, is the ability to use appropriate methodology in this respect. Such issues now constitute an integral element of public management in Poland. Research Design & Methods: A cognitive gap, identified in the scholarly literature, has served as a starting point for the theoretical and conceptual discussions addressed in this paper, in particular, within the scope of risk management methods. This paper contains a review of the literature on this subject. Deduction and induction have been used to formulate the conclusion. Another method employed in this paper is synthesis. The conclusions drawn in this paper result also from the observations made during long-term research into risk, including in the public construction sector, which has been conducted by the author at the University of Economics in Katowice. Findings: The concept proposed in this paper is the outcome of the author’s studies, conducted with a view to identifying solutions, both theoretical and methodical ones, in the area of risk management in municipal construction enterprises operating in Poland. Integrated risk management provides the basic framework for the concept which is drawn up as a result of the research. Implications / Recommendations: In its main body this paper presents a recommendation which consists of a modification of the general concept of Construction Risk Management (CRM) into Integrated Construction Risk Management (ICRM), with a simultaneous proposal that the general risk management concept (theory), which is followed by commercial companies (Enterprise Risk Management; ERM), should be implemented in municipal construction enterprises as well. The proposed solutions may then be transferred to the practical operations of such municipal entities or of public organisations at large (the utilitarian dimension of knowledge). Contribution / Value Added: This paper is an attempt to add to the theoretical background to risk management in the public sector, which refers, in particular, to New Public Management (NPM), the notion used by municipal construction enterprises in Poland. Article Classification: conceptual article JEL classification: D81, H4, H76, L7, L32